2010
DOI: 10.1039/c0ee00126k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polyketones with N-cyclic structure as electrode material for electrochemical energy storage: case of tetraketopiperazine unit

Abstract: International audiencePursuing the electrochemical evaluation vs. Li of carbonyl-based cyclic structures deriving from the oxocarbon family, polyketones with N-cyclic structure are investigated to probe the potential modifications. In this communication, we specifically report on the electrochemical investigation of our first selected family of heterocycles based on the 2,3,5,6-tetraketopiperazine unit. Working in a systematic way, a series of tetraketopiperazine molecules with quite different R groups as subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 21 publications
4
92
0
Order By: Relevance
“…Again, polymeric materials were mainly reported in the literature to circumvent the solubility issues. 191,192 However, in the latter case, the use of a viscous gel polymer electrolyte was necessary to achieve reasonable results. 188 Nokami et al reported a polymer-bound pyrene-4,5,9,10-tetraone (PPYT, Figure 6.8(b)) showing remarkable chargeedischarge properties with a high specific capacity of 231 mAh/g, even at a 30 C-rate.…”
Section: Particular Case Of the Redox-active C ¼ O Moietymentioning
confidence: 99%
“…Again, polymeric materials were mainly reported in the literature to circumvent the solubility issues. 191,192 However, in the latter case, the use of a viscous gel polymer electrolyte was necessary to achieve reasonable results. 188 Nokami et al reported a polymer-bound pyrene-4,5,9,10-tetraone (PPYT, Figure 6.8(b)) showing remarkable chargeedischarge properties with a high specific capacity of 231 mAh/g, even at a 30 C-rate.…”
Section: Particular Case Of the Redox-active C ¼ O Moietymentioning
confidence: 99%
“…There is currently a high demand for lightweight, inexpensive, flexible, and environmentally friendly energy storage devices for a number of applications including new types of portable electronics, propulsion of all-electric or hybrid vehicles as well as for the management of intermittent renewable energy sources [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…They are reduced in the voltage range of 1.5 to 2.5 V vs Li + /Li and are also potential cathode materials for rechargeable batteries. [76,77] One notable characteristic is the high initial reduction potential of organic radicals (>3 V vs Li + /Li), which is the highest among carbonyl electrodes. However, only half of the carbonyls can be reversibly reduced, leading to a practical capacity lower than 250 mAh g -1 .…”
mentioning
confidence: 99%